2021
DOI: 10.1523/eneuro.0241-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Localization of Linear Probe Electrode Arrays across Multiple Brains

Abstract: We thank the Mouse Imaging Center at The Hospital for Sick Children in Toronto for the MRI of the brains. Rob Campbell for providing technical assistance and maintenance of the SBF2P microscope. Andrew Recknagel, Tiago Ferreira and Jayaram Chandrashekar from the Mouselight team at Janelia for invaluable advice on brain clearing. Tim Harris Lab at Janelia for support with the Neuropixels probe recordings. The vivarium staff at the Janelia Research Campus for excellent animal care. Britton Sauerbrei, Ilana Witte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 91 publications
(169 reference statements)
1
23
0
Order By: Relevance
“…A small craniotomy (diameter, 0.5 -1 mm) was made over the recording sites one day prior to the first recording session. Extracellular spikes were recorded using Janelia silicon probes (HH-2) with two shanks (32 channels each, 25 mm interval between channel, 250 mm between shanks), or Neuropixels probes (Jun et al, 2017b;Liu et al, 2021;Steinmetz et al, 2021). For the HH-2 probe, 64 channel voltage signals were multiplexed, recorded on a PCI6133 board (National instrument), and digitized at 400 kHz (14 bit).…”
Section: Extracellular Electrophysiologymentioning
confidence: 99%
“…A small craniotomy (diameter, 0.5 -1 mm) was made over the recording sites one day prior to the first recording session. Extracellular spikes were recorded using Janelia silicon probes (HH-2) with two shanks (32 channels each, 25 mm interval between channel, 250 mm between shanks), or Neuropixels probes (Jun et al, 2017b;Liu et al, 2021;Steinmetz et al, 2021). For the HH-2 probe, 64 channel voltage signals were multiplexed, recorded on a PCI6133 board (National instrument), and digitized at 400 kHz (14 bit).…”
Section: Extracellular Electrophysiologymentioning
confidence: 99%
“…To our knowledge, there has been only a single report of this type of analysis using whole-brain microscopy. Liu et al (2020) 13 used light sheet microscopy to image electrophysiological probes and a semi-automated approach to align the images to an atlas (CCFv3). However, while the accuracy of their approach is comparable to that reported here, it is specific to linear electrophysiological probes and the software is not publicly available.…”
Section: Discussionmentioning
confidence: 99%
“…Then each recording channel along the Neuropixels probe (and associated neurons) was assigned to a unique CCFv3 structure. Other studies have reported better than 0.1 mm accuracy for electrode localization following similar methods (Liu et al, 2021).…”
Section: Ex Vivo Imaging and Localization Of Electrodesmentioning
confidence: 91%
“…Because each CCFv3 coordinate corresponds to a unique brain region, the precision of brain region assignments is determined by the resolution of the CCFv3, which was 25 ÎŒm per pixel. For each Neuropixels probe the locations of major structural boundaries along the track was manually aligned with the physiology data (Liu et al, 2021; Siegle et al, 2021). Then each recording channel along the Neuropixels probe (and associated neurons) was assigned to a unique CCFv3 structure.…”
Section: Methodsmentioning
confidence: 99%